2013
DOI: 10.2175/106143012x13373575831475
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Extraction of Microorganisms from Water‐Saturated, Packed Sediment

Abstract: Microbial characterization of aquifers should combine collection of suspended and attached microorganisms (biofilms). This study investigated chemical extraction of microorganisms from water-saturated, packed sediment containing established biofilms. It compares the use of different detachment-promoting agent (DPA) solutions with tap water as eluent in column experiments. Extraction efficiency was determined from cell concentrations in the column effluent. Adenosine triphosphate concentrations were measured to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…observed that solutions of NaCl and CaCl 2 showed a slower and more prolonged response similar to that described in this paper (Ugolini et al, 2013). Each of the solutions employed in this study promotes biofilm detachment and dispersal through different mechanisms.…”
Section: Optimisation Of Pre-treatments For Biofilm Detachmentsupporting
confidence: 79%
See 2 more Smart Citations
“…observed that solutions of NaCl and CaCl 2 showed a slower and more prolonged response similar to that described in this paper (Ugolini et al, 2013). Each of the solutions employed in this study promotes biofilm detachment and dispersal through different mechanisms.…”
Section: Optimisation Of Pre-treatments For Biofilm Detachmentsupporting
confidence: 79%
“…The five dispersants used clustered according to three different extraction patterns similar to those previously observed by Ugolini et al, (2013), where a Tween mix (1% Tween 80 in 0.1 M EDTA and 0.1M TSPP 2 ) was tested, among other dispersants, to detach biofilm from freshwater sediment columns. The solution released the majority of cells shortly after application, followed by drastic, rapid attenuation of its extraction efficiency.…”
Section: Optimisation Of Pre-treatments For Biofilm Detachmentmentioning
confidence: 96%
See 1 more Smart Citation
“…Miscellaneous. Ugolini et al (2013) investigated chemical extraction of microorganisms from watersaturated, packed sediment containing established biofilms.…”
Section: Assessing and Tracking Algal Blooms Andmentioning
confidence: 99%
“…Thus, both increasing the external force (e.g., by mechanical shear or sonication) or reducing the biofilm cohesiveness (e.g., by application of heat or chemical treatment) may promote detachment. Chemical detachment of biofilms from water saturated, undisturbed sediment has been previously tested in column experiments under controlled laboratory conditions (Ugolini et al ), yielding up to 8‐fold increase in cell‐extraction efficiency, and showing substantial variability in the extracted microbial community composition related to the chemical agent employed for the detachment. Conversely, detachment mediated by physical means was more effective, and resulted in a better representation of the biofilm community, especially when ultrasonication was used to promote detachment (Ugolini et al submitted).…”
Section: Introductionmentioning
confidence: 99%